The Structure of Reformulation o algo así in the Corpus oral y sonoro del español rural (COSER): Syntactic Construction, Semantic Meaning and Discursive Value - Sánchez Jiménez, Santiago U. (Círculo de Lingüística Aplicada a la Comunicación, 2020)
This article aims to analyze the functioning of the structure of reformulation o algo así in the COSER (Corpus oral y sonoro del español rural). The analysis of this construction attends to three levels: its semantic nature, the syntactic environment in which the operation of reformulation is framed and the discursive value that this structure assumes within the framework of a communicative exchange that conforms to the scheme of the semi-directed interview, discursive genre conditionated by the communicative aims pursued by the participants in this interaction: interviewer and informant.